2011
DOI: 10.1371/journal.ppat.1002300
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Nuclear Noncoding RNA Binds Re-localized Poly(A) Binding Protein and Is Required for Late KSHV Gene Expression

Abstract: During the lytic phase of infection, the gamma herpesvirus Kaposi's Sarcoma-Associated Herpesvirus (KSHV) expresses a highly abundant, 1.1 kb nuclear noncoding RNA of unknown function. We observe that this polyadenylated nuclear (PAN) RNA avidly binds host poly(A)-binding protein C1 (PABPC1), which normally functions in the cytoplasm to bind the poly(A) tails of mRNAs, regulating mRNA stability and translation efficiency. During the lytic phase of KSHV infection, PABPC1 is re-localized to the nucleus as a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(147 citation statements)
references
References 76 publications
11
133
1
Order By: Relevance
“…Data from our laboratory and others indicated that PAN RNA is a major regulator of viral gene expression through a mechanism that involves a direct interaction with the viral chromosome (5,7). PAN RNA interacts with the demethylases UTX and JMJD3 to remove the suppressive H3K23me3 mark within the KSHV viral genome.…”
mentioning
confidence: 89%
“…Data from our laboratory and others indicated that PAN RNA is a major regulator of viral gene expression through a mechanism that involves a direct interaction with the viral chromosome (5,7). PAN RNA interacts with the demethylases UTX and JMJD3 to remove the suppressive H3K23me3 mark within the KSHV viral genome.…”
mentioning
confidence: 89%
“…Many other RNPs have been captured utilizing complementary oligonucleotides (Wassarman and Steitz 1991;Borah et al 2011;Simon et al 2011), an approach whose primary advantage is that no modifications to the RNA are required. Surprisingly, although EBER1 could be selected by an antisense oligonucleotide, La and L22, the best-characterized EBER1 interacting partners, were not coselected.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike MALAT1 and MEN b, PAN RNA is subjected to canonical cleavage/polyadenylation and binds PABP (Borah et al 2011). Nevertheless, five consecutive U-A•U base triples form between part of the PAN RNA poly(A) tail and a U-rich region ;120 nt upstream of the poly(A) tail (Mitton-Fry et al 2010).…”
Section: A Triple Helix Can Functionally Replace a Poly(a) Tailmentioning
confidence: 99%